Analisis Efisiensi Biaya Operasional Melalui Pengendalian Energy Cost Dan Sumber Daya Manusia Pada Periode Low Season Di Hotel Aruna Senggigi - Ida Ayu Ari Nitiyasa; Mayu Finnari; Ni Luh Ning Puspawati; Novia Rizki; Tri Hanani; Sri Bagia (Fakultas Ekonomi dan Bisnis Unram, 2026)
This study aims to analyze operational cost efficiency through energy cost control and human resource management during the low season period at Hotel Aruna Senggigi. This research uses a descriptive qualitative approach with data collection techniques including interviews, observation, and documentation. The informants in this study consist of the Chief Engineering and the Human Resources Department (HRD) manager, while supporting data were obtained from occupancy reports, energy consumption records, and staffing data. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results show that room occupancy levels have a direct impact on energy consumption, particularly electricity, which represents the largest component of hotel operational costs. During the low season, energy cost decreased by approximately 20% compared to the high season due to reduced room activity and the implementation of energy-saving strategies. From the human resource perspective, the hotel adjusts its workforce by utilizing daily workers and flexible scheduling to maintain cost efficiency. Overall, operational cost efficiency is achieved through the adjustment of operational activities without compromising service quality.